(untitled) (Conference on English Language Teaching, 2023)
This study investigated the effectiveness of TED Talks videos on Indonesian Secondary English as a foreign language (EFL) students’ listening skills. Sixty-six students of secondary school were selected randomly and assigned to two groups, namely the control group and the experimental group. This study used a quasi-experimental, pretest-posttest control group research design. A listening pre-test was given to the participants to check their initial listening skills. During a four-week treatment period, both control and experimental groups received the same lesson plan but only the experimental group was taught the TED Talks videos to see its effect on students’ listening skill improvement. The data then were analyzed by using an Independent Samples t-test. The results showed that the instruction of TED Talks videos improved students’ listening skills in the experimental group from an average of 57,37 to 71,31. The t-test result showed that the value of t observation (to) = 2,62 was bigger than the t table (tt) = 1,67 (5%) and (tt) = 2,38 (1%). In general, the result of the experimental group supported the effect of teaching TED Talks videos on students’ listening skills.